Liquid low-flow calibration rig using syringe pump and weighing tank system. (August 2016) - Doihara, Ryouji; Shimada, Takashi; Cheong, Kar-Hooi; Terao, Yoshiya
Abstract: A calibration rig consisting of a syringe pump and a weighing tank system that can operate in the flow rate range of 0.02–60 L/h was developed in this study. This paper discusses the design considerations of the calibration methods, the development of the rig, the calibration results, and the uncertainty analysis conducted on the rig. A weighing tank system that minimizes the effects of outlet tube contact and evaporation was developed. The syringe pump system was designed using a servomotor, a precise ball screw, and a linear encoder, and it was calibrated using the developed weighing tank system via the standing start and stop method over the target range of flow rates with light oil and industrial gasoline. Several flowmeters were calibrated using the syringe pump via the flying start and finish method. During the flowmeter calibration stage, the effect of the evaporation error was eliminated because the calibration rig can form a closed pipeline system. The influence of dissolved gas and the position dependence of the syringe pulse factor on the calibration accuracy were investigated experimentally. As a result, all obtained syringe pulse factors were found to be within ±0.02% of each other. The preliminary expanded uncertainties ( k =2) of the calibration rig were estimated to be 0.066% and 0.070% for mass and volumetric flows, respectively. Highlights: A calibration rig for oil flowmeters (0.02–60 L/h) was constructed. A syringe pump was designed using a servo actuator and a linear encoder. The design of the weighing tank minimized tube contact errors and evaporation. The calibrated factors of the syringe pump were within ±0.02% of each other. The uncertainties ( k =2) were evaluated to be 0.066% (mass) and 0.070% (volumetric).